DEVELOPMENT OF LEARNING ACTIVITY PACKAGES USING AUGMENTED REALITY (AR) TECHNOLOGY INTEGRATING COMMUNITY IDENTITY TO ENHANCE TECHNOLOGICAL SKILLS FOR SMALL SCHOOLS IN THE CONTEXT OF “SEA” IN NAKHON SI THAMMARAT PROVINCE - Meeplat, Nopparat; Suebsom, Korawan (Journal of MCU Nakhondhat, 2026)
The research aims to: 1) Study the context of small schools and community identity;2) Apply augmented reality technology; and 3) Compare students’ technological skills before and after learning using augmented reality technology. The integration of augmented reality technology with community identity in the learning management process is intended to enhance technological skills for small schools. This is an action research focused on collaborative learning processes. The sample consists of 48 fourth-grade students from a small school in the "Le" context, selected purposefully. Research tools include augmented reality technology and an assessment of students’ technological skills. The research findings indicate that: 1) The context of small schools faces issues related to classroom readiness and a lack of technology, such as insufficient computers, no internet connectivity, unqualified teachers, and a lack of learning resources; 2) The application of augmented reality technology stimulates students’ learning, as they show interest and engage in collaborative and enjoyable learning, creating projects that integrate community identity with augmented reality technology; and 3) The comparison of technological skills after learning through augmented reality (AR) activities showed a higher average of 9.21 with a standard deviation of 1.33 ( = 9.21, S.D. = 1.33) compared to an average of 5.36 and a standard deviation of 1.10 ( = 5.36, S.D. = 1.10) before learning. Therefore, using augmented reality technology integrated with community identity enhances students’ technological skills and fosters creativity in media creation. It is recommended that learning processes be organized across all subjects, as it significantly develops students’ information technology skills.